2016
DOI: 10.1159/000449203
|View full text |Cite
|
Sign up to set email alerts
|

Does the Number of Neoadjuvant Chemotherapy Cycles before Interval Debulking Surgery Influence Survival in Advanced Ovarian Cancer?

Abstract: Objective: To evaluate the overall survival (OS) of patients with initially inoperable advanced ovarian cancer, tubal carcinoma, or primary peritoneal carcinoma of stages III or IV undergoing neoadjuvant chemotherapy (NAC) followed by cytoreductive surgery, according to the number of cycles performed. Methods: This retrospective study was conducted in three main oncology centres in the east of France, reviewing the charts of all patients who underwent NAC between January 1, 1998 and October 31, 2012. We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 40 publications
1
36
2
1
Order By: Relevance
“…The value of defining the prognostic role of pathologic response from IDS after NACT is that this information has the potential to guide therapy. For example, given the lack of data on the ideal number of adjuvant cycles of chemotherapy following IDS, pathologic response could be explored as a means to triage patients to less or more adjuvant chemotherapy cycles after IDS . Pathologic response could also be explored as a prognostic marker to help refine a population that might benefit from treatment strategies beyond platinum doublets in the upfront setting, such as maintenance bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…The value of defining the prognostic role of pathologic response from IDS after NACT is that this information has the potential to guide therapy. For example, given the lack of data on the ideal number of adjuvant cycles of chemotherapy following IDS, pathologic response could be explored as a means to triage patients to less or more adjuvant chemotherapy cycles after IDS . Pathologic response could also be explored as a prognostic marker to help refine a population that might benefit from treatment strategies beyond platinum doublets in the upfront setting, such as maintenance bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols of these two trials specified that IDS should be performed after 3 cycles of NAC. Other recent studies have reported conflicting results for performing late IDS after >4 cycles of NAC in patients with advanced ovarian cancer [ 12 16 ]. In one previous study, IDS after >6 cycles of NAC was found to be both safe and effective, with outcomes equivalent to those reported for the standard treatment [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one previous study, IDS after >6 cycles of NAC was found to be both safe and effective, with outcomes equivalent to those reported for the standard treatment [ 13 ]. Akladios et al reported that the number of NAC cycles did not affect the survival of advanced-stage ovarian cancer patients [ 12 ], while Colombo et al reported that patients who received >4 cycles of NAC before IDS experienced poor prognosis, despite optimal debulking surgery. Similarly, Xu et al reported that patients who underwent >5 cycles of NAC experienced shorter PFS than patients who underwent <5 cycles [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of recurrent disease, including liver metastases, included repeat surgery. 58,59 Limited literature exists regarding the use of ablative therapies to treat liver metastatic disease. Gervais et al reported a high technical success in series of six patients with metastatic ovarian carcinoma to the liver treated with RFA with absent local progression for a mean of 2.5 years.…”
Section: Ovarian Carcinomamentioning
confidence: 99%